Dampak Literasi Digital Pada Generasi Z Terhadap Komunitas Sosial di Era Digital - Umdatul Mursiyah; Siti Apipah Zachroh; Baharuddin (CV. Creative Tugu Pena, 2024)
Generation Z in its 2022 US Census report states that people were born from 1997 to 2013. Meanwhile in Australia, the McCrindle Research Center Statistics Agency calls generation Z people born from 1996 to 2010. Several facts were found that generation Z social media than use the internet more often and a previous generation. So this research aims to find out to what extent generation Z, the younger generation nowadays, uses social media and the internet more often, so that today's generation is more interested in reading through digital media compared to print media. This research also uses the library research method, namely the study of literature such as journals, books and other scientific works. One of the problems that generation Z often faces today is that they are not very interested in reading literacy. In addition, they are more interested in visual learning than print media, so their interest in reading decreases every year. Based on this problem, digital literacy is one way to encourage generation Z to have an interest in reading, to make digital literacy more attractive to today's young generation. There are three innovations added to digital media, electronic book storage, online libraries and social media. It is hoped that these innovations will facilitate generation Z's access to literary media and make it more enjoyable. Research shows that 80% of Indonesian teenagers' digital literacy success is moderate. Promiscuity is also one of the causes of generation Z becoming a generation lazing around reading and communicating well, because promiscuity has both negative and positive impacts on every individual who experiences it.